The National Institutional System with Competence in Administering Customs Duties - Ciobanu, Ramona (Transilvania University Press, 2015)
Customs duties are budgetary revenues, but also important instruments in streamlining international trade. There are several types of customs duties, but their contribution in terms of value to the establishment of public funds is rather negligible. The attributions of the customs authorities are the customs control of goods and people, the establishment and collection of taxes due, fighting crime, or, to put it differently, the enforcement of customs duties. Romania has joined the movement to liberalize world trade by ratifying numerous international conventions and harmonizing its legislation with one of the European Union, whose members it is.
Keywords: customs duty; customs tariff; customs authority